The Theoretical Description for Chlorthalidone Electrochemical Sensing on Vanadium(III)Oxyhydroxide-Modified Electrode - Tkach, V. V.; Kushnir, M. V.; de Oliveira, S. C.; Ivanushko, Y. G.; Kryvetskyi, V. V.; Kryvetska, I. I.; Kryvetskyi, I. V.; Yagodynets', P. I.; da Silva, A. O.; Derevianko, N. P.; Zavhorodnii, M. P.; Serhata, N. S.; et al. (My University, 2024)
Abstract: The electroanalytical system for VO(OH)-assisted chlorothalidone electrochemical determination has been described for the first time. The electroanalytical process may be useful for pharmaceutical investigation or doping control in sports. The electrochemical process is given as a cathodic reduction, in which the sulfamide group and lactam moiety are reduced. Based on the most probable mechanism of the electrochemical process, the mathematical model confirms the efficiency of vanadium (III) oxyhydroxide as an electrode modifier. As for the stability analysis, it confirms that a mildly acidic medium, close to neutral, is the most efficient for chlorthalidone VO(OH)-assisted cathodic determination.
Keywords: chlorthalidone; electrochemical sensor; vanadium (III) oxyhydroxide; electrochemical oscillations; stable steady-state